Behavioral neutrality among employees and its impact on the relational path of administrative leaders: An exploratory study of the opinions of a sample of employees at Ibn Al-Atheer Hospital/Nineveh (International Journal of Financial, Administrative and Economic Sciences, 2026)
The current study sought to demonstrate the level of availability of the dimensions of behavioral neutrality, and then indicate the relational path of administrative leadership at the level of Ibn Al-Atheer Hospital, leading to the identification of correlations and influences between them. The study was based on a problem defined by the following question: What is the nature of the effects of the dimensions of behavioral neutrality on the relational path of administrative leadership at the level of the organization under study (Ibn Al-Atheer Hospital)? The study adopted a hypothesis stating: There are no correlations and influences between the behavioral neutrality of employees and the relational path of administrative leadership at the aggregate level. The study adopted the questionnaire as the primary tool for collecting data on the phenomenon under study. It was subjected to validity and reliability tests, and the sample included (79) individuals. A number of statistical tools were used (SPSS v26). The study reached a number of results, the most important of which is the existence of correlations and influences between the behavioral neutrality of employees and the relational path of administrative leadership at the level of the organization under study.
Keywords: Behavioral Neutrality; Relational Path; Employees; Administrative Leadership; Ibn Al-Atheer Hospital